A quantitative PCR‐based environmental DNA assay for detecting Atlantic salmon (Salmo salar L.). Issue 5 (17th July 2018) - Atkinson, Siobhán; Carlsson, Jeanette E.L.; Ball, Bernard; Egan, Damian; Kelly‐Quinn, Mary; Whelan, Ken; Carlsson, Jens
Abstract: The Atlantic salmon ( Salmo salar L.) has worldwide ecological, cultural, and economic importance. The species has undergone extensive decline across its native range, yet concerns have been raised about its invasive potential in the Pacific. Knowledge on the distribution of this species is vital for addressing conservation goals. This study presents an environmental DNA assay to detect S. salar in water samples, using quantitative polymerase chain reaction technology. Species‐specific primers and a minor groove binding probe were designed for the assay, based on the mitochondrial cytochrome oxidase I gene. The results of this study indicate that environmental DNA is a highly effective tool for detecting S. salar in situ, and could provide an alternative, non‐invasive method for determining the distribution of this species.